Clinic-Q Medical and Dental Development Business Strategy with Sustainable Development Perspective - Iik Yani Hidayati; Muhammad Firdaus; Bunasor Sanim (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2019)
This research is research related to the formation of strategy development in a clinic. The Discussion is aimed at the theme of the clinical business development strategy. In addition, the discussion will use a sustainable business development perspective. Data collected is sourced from experts with different expertise. Assessing experts were asked to provide a questionnaire assessment related to the internal environment and the external environment of the clinic. Financial statements used are from 2015 to 2017. Assessment results from experts are then adjusted to the IE Matrix to obtain the company's strategy formulation. After obtaining the strategy formulation, the best strategy for the clinic was conducted using the QSPM approach. Results of the study show that the position of the clinic-Q Medical & Dental is in quadrant 1 which means the clinic is recommended for development. In addition, based on the assessment of QSPM, it is found that the company can implement product development, integration and market penetration. On the other hand, clinics are also advised to continue to increase their role in protecting the environment.